A new species of Neenchelys (Anguilliformes: Ophichthidae: Myrophinae) from the eastern Indian Ocean - Hibino, Yusuke; Satapoomin, Ukkrit; Kimura, Seishi (Zootaxa, 2015)
A new worm eel, Neenchelys andamanensis, is described based on a single specimen collected from a depth of 520–531 m, Andaman Sea, eastern Indian Ocean. The new species is similar to N. daedalus, N. nudiceps, and N. similis in its total vertebral count and slender body, however, it differs from the latter three in having a shorter tail (60% TL vs. 70–76%), more numerous preanal vertebrae (77 vs. 59–71), and shorter pectoral fins (2.4% HL vs. 21–27%). Although the new species resembles N. mccoskeri in some proportional characters, the former species is distinguishable from the latter by its higher total vertebral count (221 vs. 172–184), position of the dorsal-fin origin (horizontal distance from the origin to a vertical through mid-anus 65% of trunk length vs. 46–59%) and width of the interorbital region (4.5% of head length vs. 8.2–16%). A revised key to the species of Neenchelys is provided.